Patterns of breast cancer locoregional relapse, metastasis, and subtypes in Ghana - Gloria Agyekum Boaitey; Rachel Martini; Brian Stonaker; Ernest Osei Bonsu; Ernest Adjei; Ishmael Kyei; Mavis Bobie Ansah; Lisa Newman; Christian Obirikorang; Melissa B. Davis; Linda Ahenkorah Fondjo (BMC Cancer)
Abstract Background Significant advances have been made in targeted therapeutics and systemic therapy regimens for breast cancer (BC) treatment over the past decade. Tumour cells can however remain in the body, leading to locoregional relapse and/or metastasis. Subtypes of BC have distinct prognostic effects and have been linked to varying risks of early locoregional relapse and metastases, response to treatment, and overall survival. Most Low- and middle-income countries (LMICs) have no registries of BC locoregional relapse and metastasis. Methods This study comprehensively reviewed, a 3-year retrospective single-centre data of female BC visiting the Komfo Anokye Teaching Hospital (KATH), Ghana to determine the prevalence of locoregional relapse and metastasis across our patient population. Prevalence of metastasis among the various BC subtypes was also determined. Results Prevalence of BC locoregional relapse and metastasis were 3.4% and 47.6% respectively. For BC patients with documented locoregional relapse (N = 36), 27.8% (CI = 15.8 − 44.0%) had relapse to the contralateral breast, 41.7% (CI = 27.1 – 57.8%) had relapse to the ipsilateral breast, and 30.6% (CI = 18.0 − 46.9%) had relapse to regional lymph nodes. For BC patients with documented metastasis (N = 503), 151 (30%) had multiple organs involvement, 141 (28%) had lung metastases, 80 (16%) had bone metastases, 45 (9%) had liver metastases, 16 (3%) had brain metastases and 70 (14%) had other metastases (ovary, uterus, spleen, peritoneum, or distant lymph nodes). Basal subtype was the most common subtype (n = 82, 41%), followed by Luminal A (n = 69, 34.5%), HER2+ (n = 37, 18.5%) and Luminal B (n = 12, 6%). Basal subtypes had the most metastasis (35%), with multiple metastasis being the most prevalent (13%). Conclusion Close to half of the patients (46%) presented with metastatic BC. BC subtypes could influence the specific metastatic site. The most common BC subtype was the Basal subtype and had the most metastases (35%), with multiple metastasis being the most prevalent (13%). These findings should serve as a guide in the management of patients to enhance early prediction and detection of locoregional relapse and metastasis for improved overall treatment outcomes.